Dynamic relationship between technological innovation and governance institutional quality toward Malaysia’s sustainable economic growth - Nurul Wahilah Binti Abdul Latif (2023)
Technological innovation is a dynamic growth factor and practical way of addressing sustainable growth challenges. The solution depends on a complex set of factors working together in parallel. Primarily, this study measures the impact of technological innovation on economic growth, incorporating the role of governance institutional quality. This study further considers the core determinants of economic growth, including capital, employment, electricity consumption, technological innovation, and governance institutional quality. In doing so, the current study applies the autoregressive distributed lag (ARDL) bound test to estimate time series data for 19842018 in the context of Malaysia. The dynamic relationship among gross domestic product, capital, employment, electricity consumption, technological innovation, governance institutional quality, and the interaction of technological innovation and governance institutional quality are examined. To do so, the F-bounds, VECM Granger causality, Toda Yamamoto causality, CUSUM, and CUSUMSQ tests are utilized. The dynamic relationships among the variables are confirmed by F-bound test. The ARDL approach is used to find elasticity values, while VECM and Toda Yamamoto are employed to generate multivariate Granger causality values. The investigation results in several interesting findings. For example, technological innovation is detrimental to economic growth in the long run. However, the role of technological innovation remains inconclusive in the short run. Interestingly, technological innovation appears to be positive and significant in elevating growth in the presence of higher governance institutional quality. Also, technological innovation found to have an impact on economic growth in connection with governance institutional quality. Meanwhile, governance institutional quality found to have a bigger impact on economic growth in connection with technological innovation. The investigation reveals that capital plays an important role in spurring growth in the long run. The findings of this study also coincide with our argument that energy is a driving factor in accelerating economic growth. In addition, the employment rate enhances economic growth in the long run. The study conducts several robustness checks by applying DOLS. The findings from the robustness check are consistent with the main findings obtained from the ARDL approach. The findings of this study provide several important policy implications for sustainable growth in Malaysia. The integrated framework between technological innovation and governance institutional quality enables sustained change. Thus, forward-thinking plans and strategic policies are practical solutions to drive Malaysia’s technological innovation progress.